KMT-2022-BLG-0086: Another Binary-lens Binary-source Microlensing Event - Chung S-J; Hwang K-H; Yee JC; Gould A; Bond IA; Yang H; Albrow MD; Jung YK; Han C; Ryu Y-H; Shin I-G; Shvartzvald Y; et al. (IOP Publishing Limited, Bristol, England, for the Institute of Physics, 2025)
We present the analysis of a microlensing event KMT-2022-BLG-0086 of which the overall light curve is not described by a binary-lens single-source (2L1S) model, which suggests the existence of an extra lens or an extra source. We found that the event is best explained by the binary-lens binary-source (2L2S) model, but the 2L2S model is only favored over the triple-lens single-source (3L1S) model by Δχ2 ≃ 9. Although the event has noticeable anomalies around the peak of the light curve, they are not enough covered to constrain the angular Einstein radius θE, thus we only measure the minimum angular Einstein radius E,min. From the Bayesian analysis, it is found that that the binary lens system is a binary star with masses of (m1, m2) = (0.46+0.25 _0.35 M , 0.75+0.55 _0.67 M ) at a distance of DL = 5.87+1.79 _1.21 kpc, while the triple lens system is a brown dwarf or a massive giant planet in a low-mass binary-star system with masses of (m1, m2, m3) = (0.43+0.35 _0.41 M , 0.056+0.047 _0.055 M , 20.84+17.04 _20.20 MJ) at a distance of DL = 4.06+3.28 _1.39 kpc, indicating a disk lens system. The 2L2S model yields the relative lens-source proper motion of μrel ≥ 4.6 mas yr−1 that is consistent with the Bayesian result, whereas the 3L1S model yields μrel ≥ 18.9 mas yr−1, which is more than three times larger than that of a typical disk object of ∼6 mas yr−1 and thus is not consistent with the Bayesian result. This suggests that the event is likely caused by the binary-lens binary-source model.